Design and implementation of a near-field focused metasurface for microwave power transmission - Han Xiong; Jin-Yun Xie; Jia-Hao Deng; Qiang Yang; Meng Suo; Huai-Qing Zhang (Results in Physics, 2023)
In this paper, a near-field focused (NFF) metasurface composed of sub-wavelength structures for microwave power transmission is designed and implemented. Through full-wave simulations, a phase-shifting unit is proposed, which covers a transmission phase range of 360°, maintains a transmission amplitude better than −1.5 dB in most regions. Accurate design of the units at different positions in the array is achieved using phase compensation theory, forming the near-field focusing metasurface. By adjusting the transmission phase of the central unit in the metasurface to 30°, higher transmission efficiency can be achieved. Simulation results indicate that the designed near-field focused metasurface has the properties of high transmission efficiency, polarization insensitivity and distance insensitivity. To verify the transmission performance of the near-field focusing metasurface, a near-field focusing experimental platform is built and the microwave power transmission efficiency is calculated. Experimental results demonstrate that the proposed metasurface enhances the power received at the receiver, increasing the transmission efficiency by 433 %. The proposed near-field focusing metasurface holds potential for applications in high-power wireless power transfer and microwave intracavity focusing.